Association of Reactogenicity with Immunogenicity of the ChAdOx1 nCoV-19 Vaccine in Patients Undergoing Hemodialysis - Ting-Yun Lin; Nai-Kuan Hung; Szu-Chun Hung (Vaccines, 2022)
The aim of our study was to determine whether local and systemic reactions following SARS-CoV-2 vaccination are predictive of immunogenicity in patients undergoing hemodialysis. We used an established questionnaire to survey 206 hemodialysis patients without prior SARS-CoV-2 infection regarding solicited local (pain, redness, and swelling) and systemic reactions (fatigue, headache, muscle and joint pain, nausea or vomiting, abdominal pain, diarrhea, and fever) within 7 days after receiving 1 dose of the ChAdOx1 nCoV-19 vaccine for SARS-CoV-2. The primary outcome was seroconversion of anti-SARS-CoV-2 IgG (≥50 AU/mL) at 28 days after vaccination. Local and systemic reactions were reported by 80 (38.8%) and 119 (57.8%) patients, respectively. A total of 138 (67.0%) patients developed an antibody response. Responders were younger, had a lower prevalence of coronary artery disease and use of immunosuppressants, and had a higher body mass index and lymphocyte count. In addition, a greater percentage of responders than non-responders reported reactogenicity. In multivariate logistic regression analyses, fever (OR 2.70 [95% CI 1.12–6.50]) and total symptom score (OR 1.33 [95% CI, 1.05–1.68], per one increase) remained strongly associated with a greater humoral response. In conclusion, higher reactogenicity may identify hemodialysis patients who are more responsive to SARS-CoV-2 vaccination.